A machine learning approach for grain crop's seed classification in purifying separation; Journal of Physics: Conference Series; Vol. 803 : Information Technologies in Business and Industry (ITBI2016) - Vlasov A. V. Andrey Vladimirovich (2017, 2017)
Title screen